OVERVIEW OF PEDICULOSIS CAPITIS RISK FACTORS IN STUDENTS OF THE THAFIZUL QUR'AN WAHDAH ISLAMIYAH ISLAMIC BOARDING SCHOOL IN MAKASSAR CITY - Rosdiana Mus; Awaluddin Awaluddin; Rabiah Rabiah (UNUSA Press, 2022)
Pediculosis capitis is a skin disease caused by the parasite pediculus humanus capitis.Some of the risk factors for this disease are infuenced by the enivironment and individual habits. This research aimed to know an overview of risk factor on pediculosis capitis for Thafizul Qur’an Wahdah Islamiah Boarding School in Makassar. The research observational research by planning of categoric descriptive. Date were collected by using primary and secondary data.The were 73 students fulging inscusive category. Case overview of pediculosis capitis by 44 (60,3%). Some risk factors affacting Pediculosis capitis were level of study, age, using of accesories alternatively, gather bedroom usage, suffer of Pedicuosis capitis in the same room, kinds of hair, long hair, hair thickness, nimber of friends at boarding school.